The impacts of training pathways and experiences during intern year on doctor emigration from Ireland - Frances Cronin; Nicholas Clarke; Louise Hendrick; Ronan Conroy; Ruairi Brugha (BMC, 2019)
Abstract Background Emigration of domestically-trained health professionals is widespread, including in Ireland which has the highest rate of medical graduates in the OECD. Ireland's failure to retain graduates necessitates high levels of international recruitment. This study aimed to identify factors associated with recently graduated doctors' intention to migrate, focusing on their work experiences during the mandatory post-graduation year, their wellbeing, and their perceptions of postgraduate training in Ireland. Methods A baseline survey was administered online to all final year students in Ireland's six medical schools. A subsequent sweep surveyed those who consented to follow-up (n = 483) during the final month of first year of practice. Results Of the 232 respondents (48% response rate), 210 (94%) were Irish passport holders. Of these, only 36% intended to remain in Ireland after their internship, 57% intended to leave but return later, and 7% intended to leave permanently. A strong predictor of intention was study pathway: 60% of Graduate Entry Medicine (GEM) graduates and 25% of Direct Entry Medicine (DEM) graduates intended to remain in Ireland. Equal proportions intended to leave permanently (8% DEM, 6% GEM). Being a GEM graduate significantly reduced the likelihood of leaving to return (relative risk ratio (RRR) 0.20, 95% confidence interval (CI) (0.11-0.39), p < 0.001). When adjusted for study pathway, a negative experience as an intern increased the likelihood of leaving to return (RRR 1.16 CI (1.00-1.34), p = 0.043) and leaving permanently (1.54 (1.15-2.04), p = 0.003). Similarly, experience of callousness was associated with leaving to return (1.23 (1.03-1.46), p = 0.023) and leaving permanently (1.77 (1.24-2.53), p = 0.002), as was burnout with leaving permanently (1.57 (1.08-2.27), p = 0.017). Those planning to specialise in Medicine versus General Practice were more likely to leave and return (3.01 (1.09-8.34), p = 0.034). Those with negative perceptions of training in Ireland were more likely to leave and return (1.16 (1.01-1.34), p = 0.037); a positive perception reduced the likelihood of leaving permanently (0.50 (0.26-0.94), p = 0.032). Conclusions Increasing GEM training places might improve Ireland's retention of domestically-trained doctors, reducing reliance on non-EU-trained doctors. However, improvements in the working experiences, perceptions of training, and protection of wellbeing are essential for retaining this highly sought-after and geographically mobile cohort.